Persepsi Guru: Kendala Implementasi Asesmen Alternatif - Nirahua, Juliana; Tamaela, Elsina Sarah; Latupeirissa, Asry N. (KAMBOTI: Jurnal Sosial dan Humaniora, 2025)
Alternative assessment is a more authentic and comprehensive assessment method compared to traditional assessment, but its implementation faces various challenges so that research is needed to answer these problems. This study aims to analyze the perceptions of teachers in Namrole District, South Buru Regency, Maluku about the obstacles to implementing alternative assessments in learning. This study uses a survey method with a quantitative descriptive approach, involving 62 teachers as respondents. Data collected through a questionnaire with seven dimensions, namely teacher understanding of alternative assessments, teacher understanding of alternative instruments, availability of supporting facilities, teacher professional development, efficiency of compiling alternative assessments, budget/funding support and colleagues/leaders and workload. The data collected were then analyzed descriptively. The results showed that 76.26% of teachers understood alternative assessments, but only 66.77% had the skills to design them. As many as 74.84% of teachers understood the assessment instruments, while 67.42% of teachers stated that the facilities and infrastructure in schools supported the implementation of alternative assessments. However, 66.21% of teachers have limited access to professional training, and 70.73% of teachers stated that efficiency in preparing alternative assessments is still a challenge. Although 70.06% of teachers agree that financial support, colleagues and leaders support implementation and as many as 71.45% of teachers are aware of challenges in implementing alternative assessments, in terms of workload. Based on the results of the study, it can be concluded that junior high school teachers in Namrole District still need assistance in preparing and implementing alternative assessments in learning.